ЛУВСАНДАНЗАНЫ “АЛТАН ТОВЧ” ДАХЬ БИЛИГ СУРГААЛЫН УТГА ТАЙЛАЛ - С.Дашдэжид, (Acta Mongolica, 2013)
]It is reasonable to search for the Chinggis Khaan’s greatest historical events and his conquers from the “Bilig surgaali”. He conquered the half of the world uniting the Mongol Empire under one politic division and became known as the great founder. Luvsandanzan’s “Altan tovch” is systematically gathered all of knowledges of the Chinggis Khaan’s “Bilig surgaali”. This source has Chinggis khaan’s proverbs targeted at his ancestors such as boys, brothers, girls and marshals. Most of proverbs estimated that leadership requirements for governing are not only strength, enthusiasm, one heartiness, endurance, ability of self-control and encouragement but also honoring knowledge and study from academician and scientist. Therefore, deep understandings of “Bilig surgaali” have been becoming clearer from every word and shining out more and more.